(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In this article we focused about Kautilya’s ideas oninter-state relations and diplomacy.Kautiiya’s Arthasastra is the precious gems of ancient Indianpolitical thought and produced at different historical settings. Kautilya’s Arthasastra havea common theme relating to the functions and duties of the king known as “Raj-Dharma.” They have a common religious background and philosophicalbasis and a common concept of Dharma. Both deal with the principles of socialconduct, administration of civil and criminal laws and also the policy offoreign relations, i.e., inter-state relations.